PELATIHAN KEWIRAUSAHAAN BAGI PELAKU UMKM DI KELURAHAN PAMMANA KABUPATEN WAJO - Yuniarti, Andi; Nurwana, Andi; Jamaluddin, Andi (Arunika: Jurnal Pengabdian Masyarakat, 2023)
Community service is the implementation of the practice of science, technology and art and culture directly to the community institutionally through scientific methodology as the dissemination of the Tri Dharma of Higher Education and a noble responsibility in efforts to develop community capabilities. MSME development is a community service activity in the form of applying science and technology results to solve problems faced by MSME units (micro, small and medium enterprises). This program is aimed at increasing the independence and performance of MSMEs. Examples include: improving the quality of MSME industrial processed products, increasing MSME productivity with appropriate technology, developing online marketing to expand the MSME market, such as only in the Pammana village, Pammana sub-district, Wajo district, with several residents trying to open a business but lacking skills. so that skills are needed so that an entrepreneurial spirit is needed. In this training, it is hoped that entrepreneurs can increase their productivity and provide knowledge to market their products online